Purification and properties of shikimate kinase II from Escherichia coli K-12. - DeFeyter, R C (1986)
Shikimate kinase II was purified to near homogeneity from an Escherichia coli strain which overproduced the enzyme. The apparent Km of this isoenzyme for shikimate was 200 microM, and for ATP it was 160 microM. The Km for shikimate is approximately 100-fold lower than the Km of shikimate kinase I, suggesting that shikimate kinase II is the isoenzyme normally functioning in aromatic biosynthesis. Shikimate kinase II is dependent on metal ions for activity.